Home,1798
includes letters from: Missionary Society, to Sweden J Van der Pouin, Lexmond [Netherlands] (Dutch with English translation by Dr Johannes Vanderkemp) - offer of service Evan Nepean [first secretary to the Admiralty, later Sir Evan Nepean], Admiralty Office - response to request for protection of Duff men from press-gang Robert Little, Hanley, Staffordshire [later Stoke on Trent] Thomas Robson, Cork [Ireland] - reporting return of the Duff Benjamin Barr, Cove of Cork (on behalf of the ship Duff's company) John Griffin, Portsea [Portsmouth, Hampshire] William Cole, Colchester - plan for a missionary magazine joint letter from George Lewis (Bala) and Morgan Jones (Newcastle Emlyn, Cardiganshire/Ceredigion) - first expression of interest from Wales William Wilson, London Alexander Waugh, Whitby J M Wildbore, Falmouth Joseph Slatterie, Chatham John Saltren, Bridport William Howell, Knaresbro' [Knaresborough, Yorkshire] John Eyre. Hackney Charles Remmington, London Joseph Hardcastle, London - to Thomas Robson on his appointment to command the Duff joint letter by S Carver and T Barrett (both nearly 18), Cornhill (London) - offering to be midshipmen on the Duff John Smith, Sheffield J Boden, Sheffield